Soft soil stabilization using crushed glass and polypropylene - Nur Hakam, Hakamazaman (2015)
The use of crushed glass and polypropylene as raw nurses are encouraged in construction. Furthermore, these materials are easy to find because it is a waste product. This method is also capable of reducing solid waste that cannot be eliminated, especially plastic. However, the utilization of these materials in civil engineering construction applications has just received some attention within the last decade. This aim of this Final Year Project is to determine the strength improvement of soft clay mixed with crushed glass and polypropylene. The optimum moisture content obtained from the standard compaction test on sample taken from Kampung Tg. Medang, Pekan Pahang. The percentage of crushed glass and polypropylene mixed with soft soil were 10%, 15%, 20% and 25% by weight of sample. Soil samples were tested in laboratory to determine their basic properties of soil. The soil sample undergo unconfined compression test before and after being treated with crushed glass and polypropylene to determine their shear strength. After undergo unconfined compression test before and after the sample being treated, the value of stress for the sample before being treated with crushed glass and polypropylene was 647.02 kN/m2.The value is calculated from the average of 4 specimens. There are differences between shear strength of the sample taken from Kg Tg Medang before and after being treated with crushed glass and polypropylene. The shear strength increase by 2.21% for additional of 5% polypropylene plus 5% crushed glass, 13.29% for additional of 5% polypropylene plus 10% crushed glass, 6.92% when added with 5% polypropylene plus 15% crushed glass and lastly increase by 5.5% when mix with 5% polypropylene plus 20% of crushed glass. The optimum content of additive is 5% polypropylene plus 10% of crushed glass which will increase the shear strength of the soft clay by 13.29% from 647.02 kN/m2 up to 733 kN/m2.